Structural Strength Analysis of a High-Density Polyethylene Floating Jetty under Ship Collision - Kharis Abdullah; Sryang T Sarena; Aditya Maharani (International Journal of Marine Engineering Innovation and Research, 2026)
Floating jetties are increasingly used in marine infrastructure because of their adaptability to water-level fluctuations and ease of installation. Recently, High-Density Polyethylene (HDPE) has attracted attention as an alternative construction material due to its corrosion resistance, lightweight characteristics, and impact-absorption capability. However, information regarding the structural behaviour of HDPE floating jetties under ship collision loads remains limited. Therefore, this study aims to investigate the structural response and deformation characteristics of an HDPE floating jetty subjected to vessel berthing impacts. The analysis was conducted using the Finite Element Method (FEM). A floating jetty with dimensions of 10 m × 2.5 m × 1.5 m was modelled and subjected to collision loads generated by a 5-ton vessel approaching at a 20° berthing angle. Berthing energies were calculated according to PIANC recommendations and converted into equivalent static impact loads under favourable, moderate, and unfavourable berthing conditions. The calculated berthing energies were 88.4 J, 198.9 J, and 353.6 J, corresponding to impact loads of 15.2 kN, 22.7 kN, and 30.2 kN, respectively. The maximum deformations obtained from the FEM analysis were 12.11 mm, 18.21 mm, and 24.22 mm. The results showed a nearly linear relationship between impact load and structural deformation, indicating stable elastic behaviour throughout the investigated loading range. Even under the most severe berthing condition, the maximum deformation represented only 0.24% of the jetty length. The study demonstrates that HDPE floating jetties possess adequate impact resistance and deformation capacity for small-vessel berthing operations. These findings provide additional insight into the application of HDPE as a structural material for floating marine infrastructure subjected to collision loading.